Evaluation and Implementation of WISE-4051-AE Communications in Process Level Laboratory Module - Heru Wijanarko; Hermanto Simanungkalit; Asrizal Deri Futra; Aditya Gautama Darmoyono; Nanta Fakih Prebianto; Muhammad Syafei Gozali (Politeknik Negeri Malang, 2023)
This research discusses the design and implementation of wireless communication using WISE-4051-AE for optimizing process-level practical modules. The WISE-4051-AE wireless device is an integrated IoT (Internet of Things) device that combines data acquisition, processing, and control functionalities. Continuing previous research, this study focuses on creating practical modules for process control, including flow meter calibration, cascade control, feedforward control, and ratio control. By utilizing the WISE-4051-AE wireless device in a plant setting, the processed data can be accessed through laptops, personal computers, and other devices that support communication with the WISE-4051-AE device. To get the data, a device must be connected to the WISE-4051-AE wireless device. By employing the WISE-4051-AE wireless device for data transmission, users of the process-level practical modules can receive real-time plant data, regardless of whether the modules are indoors or outdoors, without encountering any data alteration during the transmission process. In this research, the WISE-4051-AE wireless device has a maximum range limitation. As long as the user's device remains within the signal range of the WISE-4051-AE device, the transmitted data will not undergo any changes. The signal range was tested under two conditions: without signal obstacles and with signal obstacles. The results of the signal range testing revealed a maximum range of 90 meters without obstacles and 40 meters with obstacles.